ROLE OF GENERICS IN TREATMENT OF HEPATITIS C INFECTION - Umar, Muhammad; Akhter, Tayyab Saeed; Akbar, Ibrar; Nisar, Gul; Osama, Muhammad (Journal of Ayub Medical College Abbottabad, 2017)
With the discovery of newer and newer DAAs, the cure of Hepatitis C seems to be a reality. But their high price and availability is a big hindrance. Sofosbuvir launched byGileadcosts about $ 84000 per 12-week course. Since its launch there is a huge debate regarding the complex pricing mechanism of DAAs. The pricing involves negotiation of patent holder with health insurance companies through their Pharmacy Benefit Managers (PBMs). Several rebates are also involved in this pricing mechanism amongst which only few are declared ones. Different countries are adapting different strategies to overcome this pricing issue. The branded companies have also issued licenses to companies to form generic version of the drugs and to market them to selected middle and low income countries. Few countries that are not in the list have rejected the patent and started producing their own generics. It is due to these generics that the price of DAAs had undergone a significant reduction but their manufacturing and efficacy needs regular scrutiny. Keywords: Generics, Pricing; Direct Acting Antivirals (DAAs); Hepatitis C Virus